2020
DOI: 10.1007/s00066-020-01646-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemotherapy with or without cetuximab for unresectable esophageal cancer: final results of a randomized phase 2 trial (LEOPARD-2)

Abstract: Purpose To investigate the efficacy and toxicity of cetuximab when added to radiochemotherapy for unresectable esophageal cancer. Methods This randomized phase 2 trial (clinicaltrials.gov, identifier NCT01787006) compared radiochemotherapy plus cetuximab (arm A) to radiochemotherapy (arm B) for unresectable esophageal cancer. Primary objective was 2‑year overall survival (OS). Arm A was considered insufficiently active if 2‑year OS was ≤40% (null hypothesis = H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Studies have shown that the survival rate of tumors located in the upper, middle, and lower esophagus is different, the prognosis of upper esophageal cancer is worse than that of middle esophagus and lower esophagus. 9 Fifth, in Table 1, the difference in tumor stage between the two groups was statistically significant. Similarly, in the multivariate analysis, the difference in tumor stage between the two groups was also statistically significant.…”
Section: Effect Of Perioperative Flurbiprofen Axetil On Long-term Survival Of Patients With Esophageal Carcinoma Who Underwent Thoracoscomentioning
confidence: 89%
“…Studies have shown that the survival rate of tumors located in the upper, middle, and lower esophagus is different, the prognosis of upper esophageal cancer is worse than that of middle esophagus and lower esophagus. 9 Fifth, in Table 1, the difference in tumor stage between the two groups was statistically significant. Similarly, in the multivariate analysis, the difference in tumor stage between the two groups was also statistically significant.…”
Section: Effect Of Perioperative Flurbiprofen Axetil On Long-term Survival Of Patients With Esophageal Carcinoma Who Underwent Thoracoscomentioning
confidence: 89%
“…We excluded one RCT because it had a sample size far below the statistical requirements and thus had a high risk of bias (Figure S1). 11 Finally, we included 7 RCTs [12][13][14][15][16][17][18] and 10 retrospective studies [19][20][21][22][23][24][25][26][27][28] for trial-and treatment armlevel analyses (Tables S1 and S2). Patient survival in the RCTs was superior to that in the retrospective studies, regardless of the time point (1-, 2-, and 3-year PFS and 5-year OS).…”
Section: External Validation Of the Association Between Os And Pfsmentioning
confidence: 99%
“…OS of patients with HER2-positive stomach cancer is higher with trastuzumab deruxtecan (a conjugate consisting of trastuzumab and a cytotoxic topoisomerase I inhibitor) therapy than with irinotecan or paclitaxel chemotherapy (12.5 vs. 8.4 months) [20]. In patients with unresectable esophageal cancer, OS tends to be longer when treated with cetuximab in combination with radiochemotherapy compared to radiochemotherapy alone (49.1 vs. 24.1 months) [21].…”
Section: Conventional and Potential Targeted Therapy Against Metastatic Circulating Tumor Cellsmentioning
confidence: 99%
“…However, current therapeutic strategies mainly target the primary tumor, assuming that metastatic seeds will also be killed. Indeed, several drugs, for example EGFR tyrosine kinase inhibitors and anti-HER2 monoclonal antibodies, can suppress metastasis and improve the survival of cancer patients [19,21]. Nevertheless, this is rather an exception than the rule; most anticancer therapies only indirectly affect metastasis-initiating cells.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%